Addressable DNA nanotubes with repetitive components. Issue 48 (28th November 2019) - Bai, Tanxi; Wei, Bryan
Abstract : We present a new strategy to produce DNA nanotubes based on canonical SSTs with addressability available along the axial direction of the self-assembled tubes, which are also programmably repetitive along the lateral direction. Abstract : Extended DNA nanostructures have already been constructed in a repetitive arrangement from millions of building blocks, many more than currently feasible with even the gold standard of addressable self-assembled structures. In order to construct addressable DNA nanostructures with more building blocks, it is desirable to arrange the addressable components repetitively. Accordingly, the overall size of the structure can be multiplied by the level of repetition in the addressable strands. In this study, we present a nanotube system that combines two seemingly conflicting features: addressability and repetitiveness. Based on an understanding of the tubulation resulting from the intrinsic curvature of the components, we produce DNA nanotubes with addressability available along the axial direction of the self-assembled tubes, which are also programmably repetitive along the lateral direction.